Realization of different diversity technique for mimo based mobile ad-hoc network using space time block codes - Chowdhuri, Swati; Byabartal, Nilanjan; Choudhury, Dr. S.S.; Banerjee, Dr. P.K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
With the fast progress of MIMO technology and its growing applications in the mobile ad hoc networks, it is important to develop a technique to enable more efficient MIMO implemented mobile ad hoc network. The simple, yet powerful concept of an bit error rate (BER) performance calculation with respect to bit energy to noise spectral density ratio (Eb/N0) of a typical transmit diversity scheme with various number of transmit and receiving antennas. Different diversity technique for mimo based mobile ad hoc network using space time block codes are demonstrated to show the superiority in performance of MIMO over single-antenna routing schemes, particularly at high SNR.